2021
DOI: 10.1039/d1gc00311a
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable production of 5-hydroxymethyl furfural from glucose for process integration with high fructose corn syrup infrastructure

Abstract: 5-hydroxymethyl furfural (HMF) is a platform chemical, which can be derived from lignocellulosic biomass, and used for production of liquid fuels and polymers. We demonstrate a process for production of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 31 publications
0
48
0
Order By: Relevance
“…153,154 For example, adding acetone to the aqueous phase improved the rate of fructose dehydration, but reduced the sugar solubility. 155,156 While a high reaction rate is beneficial, lowering the solubility of the sugar will result in a feed at a lower sugar concentration, which can be a disadvantage for an industrial-scale process design. 38 When the starting material is not a solution of sugar in water but solid biomass (e.g., lignocellulose), its impregnation with the solvent will affect the hydrolysis process.…”
Section: Outlook On the Effects Of Polar Aprotic Solvents Effect On Starting Materials And Productsmentioning
confidence: 99%
See 2 more Smart Citations
“…153,154 For example, adding acetone to the aqueous phase improved the rate of fructose dehydration, but reduced the sugar solubility. 155,156 While a high reaction rate is beneficial, lowering the solubility of the sugar will result in a feed at a lower sugar concentration, which can be a disadvantage for an industrial-scale process design. 38 When the starting material is not a solution of sugar in water but solid biomass (e.g., lignocellulose), its impregnation with the solvent will affect the hydrolysis process.…”
Section: Outlook On the Effects Of Polar Aprotic Solvents Effect On Starting Materials And Productsmentioning
confidence: 99%
“…1,[168][169][170] Additionally, it is reported that the use of some aprotic organic solvents (e.g., dioxane) negatively affects the solubility of sugars in the feed. 155,156 This could lower the overall production rate, if it forces to operate at sugar concentrations that are below the desired level, e.g., as dictated for good selectivity. 156 Typically, a general industrial criterion for reactor productivity indicates a minimum rate of 100 g/L/h.…”
Section: Application Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…The valorization of renewable resource, especially biomass and its based compounds to produce value-added chemicals and fuels as well as pharmaceutically relevant compounds in more efficient and sustainable manner continues to be an important goal of chemical research. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] In this regard the development of resourceful and cost-effective catalytic methodologies to convert biomass and its derived feedstock to essential products is of central importance. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Among sugar derived feedstocks, 5hydroxymethylfurfural (HMF) represents highly valuable platform compound, [20][21][22][23][24][25] which has been listed as the top 10 renewable chemicals by the U.S. Department of Energy.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] In this regard the development of resourceful and cost-effective catalytic methodologies to convert biomass and its derived feedstock to essential products is of central importance. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Among sugar derived feedstocks, 5hydroxymethylfurfural (HMF) represents highly valuable platform compound, [20][21][22][23][24][25] which has been listed as the top 10 renewable chemicals by the U.S. Department of Energy. [22][23] Notably, HMF serves as renewable feedstock to produce valueadded chemicals, fuels, and polymers.…”
Section: Introductionmentioning
confidence: 99%